n-Butanol production by Rhodopseudomonas palustris TIE-1 - Wei Bai (Nature Portfolio, 2021)
Bai et al show that the anoxygenic phototroph strain TIE-1 can produce n-butanol using organic acids or CO2 as a carbon source, light as an energy source, and H2, Fe(II), or electrons from renewably generated electricity as an electron source. This study opens the possibility of producing carbon-neutral biofuels using these bacteria.